Protection of Human Right for Pregnant Women in Implementing HIV/AIDS Screening for Prevention of HIV/AIDS transmission from mother to Child in Bantul District Health Center - Tyan Ferdiana Hikmah; Agnes Widanti; I. Edward Kurnia SL (SOEPRA, 2019)
HIV / AIDS is a health problem in the world which is constantly increasing, especially in women during pregnancy. The government has made efforts to prevent the spread of HIV / AIDS from mother to child where one of its components is to screen for pregnant women. Implementation of HIV / AIDS screening at Puskesmas Bantul District still focuses on increasing coverage of visit in Puskesmas, not yet paying attention to how the protection of human rights for pregnant women.The research method was sociological juridical, with descriptive analytical specification. Primary data were obtained from interviews with 4 midwifes, 4 persons in charge of the program, 4 heads of community health centers and 4 heads of health center and 1 person in Health Office’s Bantul District and 8 pregnant women as well as observation at four health centers in Bantul district. Secondary data were legal materials, official documents, books and research journals. Data analysis using qualitative was inductive.Implementation of HIV / AIDS screening for pregnant women is regulated in Minister of Health Regulation Number 97, 2017 and Minister of Health Regulation Number 51, 2013 about prevention of mother to child transmission of HIV / AIDS related to the protection of human rights for pregnant women. The protection of human rights for pregnant women in the implementation of HIV / AIDS screening at the Bantul District Health Center has not been fulfilled in terms the rights of information, the rights of consent, and the rights of confidentiality. Supporting factors include the availability of health facilities, supporting health resources, supporting facilities and infrastructures while inhibiting factors are health services, limited number of counselors, social support (husbands, health workers, community leaders), affordability, pregnant women working, knowledge, social factors, and the implementation of legislation.